Transfusion practices for pediatric oncology and hematopoietic stem cell transplantation patients: Data from the National Heart Lung and Blood Institute Recipient Epidemiology and Donor Evaluation Study‐III (REDS‐III). Issue 9 (29th August 2021) - Goel, Ruchika; Nellis, Marianne E.; Karam, Oliver; Hanson, Sheila J.; Tormey, Christopher A.; Patel, Ravi M.; Birch, Rebecca; Sachais, Bruce S.; Sola‐Visner, Martha C.; Hauser, Ronald G.; Luban, Naomi L. C.; Gottschall, Jerome; et al.
Abstract: Background: To evaluate transfusion practices in pediatric oncology and hematopoietic stem cell transplant (HSCT) patients. Study design and methods: This is a multicenter retrospective study of children with oncologic diagnoses treated from 2013 to 2016 at hospitals participating in the National Heart Lung and Blood Institute Recipient Epidemiology and Donor Evaluation Study‐III. Transfusion practices were evaluated by diagnosis codes and pre‐transfusion laboratory values. Results: A total of 4766 inpatient encounters of oncology and HSCT patients were evaluated, with 39.3% (95% confidence interval [CI]: 37.9%–40.7%) involving a transfusion. Red blood cells (RBCs) were the most commonly transfused component (32.4%; 95% CI: 31.1%–33.8%), followed by platelets (22.7%; 95% CI: 21.5%–23.9%). Patients in the 1 to <6 years of range were most likely to be transfused and HSCT, acute myeloid leukemia, and aplastic anemia were the diagnoses most often associated with transfusion. The median hemoglobin (Hb) prior to RBC transfusion was 7.5 g/dl (10–90th percentile: 6.4–8.8 g/dl), with 45.7% of transfusions being given at 7 to <8 g/dl. The median platelet count prior to platelet transfusion was 20 × 10 9 /L (10–90th percentile: 8–51 × 10 9 /L), and 37.9% of transfusions were given at platelet count of >20–50 × 10 9 /L. The median international normalized ratio (INR) prior to plasma transfusion was 1.7 (10–90th percentile: 1.3–2.7), and 36.3% of plasma transfusions were given at an INR between 1.4 and 1.7. Discussion: Transfusion of blood components is common in hospitalized pediatric oncology/HSCT patients. Relatively high pre‐transfusion Hb and platelet values and relatively low INR values prior to transfusion across the studied diagnoses highlight the need for additional studies in this population.